Analisis Kinerja Biaya dan Waktu pada Pembangunan Pasar Sentral Kabupaten Majene Sulawesi Barat - amir, mardiana (FORUM BANGUNAN, 2013)
In this study the authors use a method that is based on the concept of the value of the three indicators , namely : BCWS , BCWP , and ACWP . Budgeted Cost of Work Schedule ( BCWS ) , and identification method variance , thus producing estimates the cost and the length of time until the end of the execution of a project . The results showed Based on the concept of the value of the method can be concluded that the project 12 weeks experienced a gain of Rp 1,425,418,200 ( BCWP - ACWP ) or 15 % of the total cost of the project budget and project implementation faster one week of the project plan . Based on the indicators available at the time of reporting that at week 12 , it can be concluded that the Cost Variance obtained is Rp . 1,325,418,200.00 which shows that ( CV > 0 ) means the project cost less than the cost of the plan ( experience gains ) and Schedule Variance obtained is Rp . 688,761,000.00 which shows that ( SV > 0 ) means the project run faster than the planning time. Keywords : cost, time, BCWS , BCWP , and ACWP